Analysis of the stability control of the car with the admission to the infrastructure - T. A. Antropova; M. I. Glushko (Вестник Научно-исследовательского института железнодорожного транспорта, 2018)
The rolling stock and the railway track are a single stant tendency of the development of rail transport in relation to mechanical system. The running parts of the rolling stock and the the interaction of the power wheel-to-rail friction pair consists in track are interacting under difficult dynamic conditions. The con-increasing the axle load on the rails for freight rolling stock and further increasing the speed of the passenger trains. It takes a qualified approach to traffic safety issues and special attention to the stability of rolling stock to achieve these goals. An analysis of the stability control of the car with an admission to the infrastructure was carried out based on the regulatory documents that establish the main provisions and procedures for the operation of railways and railway workers. Authors proposed the elimination of existing shortcomings and ensuring the stability of the carriage motion by optimizing parameters of the placement of goods in the car. Calculations were made on the rollover stability conditions (stability loss) of the body and the criterion of the critical speed at which the carriage derailed due to the loss of contact of the wheels with the internal rail line of the curve. A method for controlling the stability of a car with a load by means of two-position weighing is proposed. The results obtained also make it possible to determine the height of the common center of gravity (CG), the magnitude of the longitudinal and lateral displacement of the center of gravity of the freight.